Safety assessment of Edaravone: A real-world adverse event analysis based on the FAERS Database - Ziyue Wang; Bowen Lu; Hao Yang; Weijie Zhao; Xinru Kong; Chuanhao Mi; Jianlin Wu (PLoS ONE, 2025)
Objective Edaravone is a neuroprotective agent, but the characteristics of its adverse events (AEs) remain insufficiently explored. This study aims to examine AEs associated with edaravone use by analyzing real-world data from the FDA Adverse Event Reporting System (FAERS). Methods This retrospective study extracted adverse event reports related to edaravone from the FAERS database, spanning from the second quarter of 2017 to the second quarter of 2024. Disproportionality analysis methods, including the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), and Bayesian Confidence Propagation Neural Network (BCPNN), were employed to detect AE signals associated with edaravone use. Results Among 2,931 adverse event reports (AERs) in which edaravone was identified as the primary suspected drug, 86 preferred terms (PTs) and 20 system organ classes (SOCs) were included. At the PTs level, the significant drug-related adverse events were death (n = 589, ROR = 8.64), disease progression (n = 266, ROR = 28.26) and drug ineffectiveness (n = 252, ROR = 2.16). Additionally, rare but notably strong adverse event signals were observed, including thrombosis at the catheter site thrombosi, gastric fistula, and vein collapse. Conclusion Our research found that edaravone has some overlooked adverse reactions. Further epidemiological studies are needed to more comprehensively explore and assess the risk-benefit profile of edaravone.